2023
DOI: 10.1021/acsenergylett.3c00427
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Mixed Halide Perovskite Nanocrystals

Abstract: Colloidal mixed halide perovskite nanocrystals (NCs) irreversibly degrade when exposed to ultraviolet−visible irradiation. Here, mixed halide perovskite NC photolysis is tracked via mass spectrometry, electron microscopy, and photoluminescence. The data shows continuous wave ultraviolet−visible irradiation causes the heavier halides within the alloy to sublimate. This ultimately transforms CsPb(I 1−x Br x ) 3 and CsPb(Cl 1−x Br x ) 3 (x ≈ 0.50) NCs into CsPbBr 3 and CsPbCl 3 NCs, respectively. Time-resolved ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Charge carrier trappings at halide interstitials are now well-accepted in LHPs. These trappings create a large amount of halide vacancies and increase the ionic conductivity by several orders of magnitude under illumination, and they facilitate halide segregation. Photocarrier trappings preferentially happen at iodide interstitials in mixed I–Br perovskites due to higher trapping barrier at bromide interstitials, rooted in the higher electronegativity of bromine over iodine. I 2 is also a product of photocarrier trapping at iodide interstitials, ,,, whose exclusion to the grain boundary followed by its reduction is also suggested to cause the halide segregation. ,, Very recently, we demonstrated that the photogenerated I 2 can redistribute and combine with negatively charged bromide (Br – ) in the perovskite to form a triple halide ion of I 2 Br – (I δ− -I δ+ -Br δ− ), whose negatively charged iodide (I δ− ) can further exchange with another lattice Br – to form the I-rich phase . There is a general consensus that photocarrier trappings at iodide interstitials dominantly affect halide segregation, and indeed it has been demonstrated that this photoinstability is ceased by deactivating the trapping capability of iodide interstitials by modulating their energy level relative to the valence band edge. …”
mentioning
confidence: 99%
“…Charge carrier trappings at halide interstitials are now well-accepted in LHPs. These trappings create a large amount of halide vacancies and increase the ionic conductivity by several orders of magnitude under illumination, and they facilitate halide segregation. Photocarrier trappings preferentially happen at iodide interstitials in mixed I–Br perovskites due to higher trapping barrier at bromide interstitials, rooted in the higher electronegativity of bromine over iodine. I 2 is also a product of photocarrier trapping at iodide interstitials, ,,, whose exclusion to the grain boundary followed by its reduction is also suggested to cause the halide segregation. ,, Very recently, we demonstrated that the photogenerated I 2 can redistribute and combine with negatively charged bromide (Br – ) in the perovskite to form a triple halide ion of I 2 Br – (I δ− -I δ+ -Br δ− ), whose negatively charged iodide (I δ− ) can further exchange with another lattice Br – to form the I-rich phase . There is a general consensus that photocarrier trappings at iodide interstitials dominantly affect halide segregation, and indeed it has been demonstrated that this photoinstability is ceased by deactivating the trapping capability of iodide interstitials by modulating their energy level relative to the valence band edge. …”
mentioning
confidence: 99%
“…This can be justified since the reported activation barriers for ionic migration of iodide vacancies (360 meV) are significantly higher than for bromide vacancies (270 meV) in CsPbX 3 perovskites . In addition, the dissociation energies of the Pb-X bond increase with the halide electronegativity such that Pb–I (194 kJ mol –1 ) < Pb–Br (248 kJ mol –1 ) < Pb–Cl (301 kJ mol –1 ) . Consequently, it becomes challenging for Br – to return from the bulk film to the QDs layer. , Hence, the thermodynamic stabilization of this interface between the 3D and QDs can be attributed to the formation of more rigid [PbX 6 ] 4– frameworks in the 3D interfacial layers .…”
mentioning
confidence: 99%